Penerapan Pengelolaan Pembelajaran Bilingual di SMP ZIIS Cilongok, Banyumas - Ichwan Hero Handriyanto; Alief Budiyono (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
Bilingual learning is learning two languages, in which mother tongue and foreign language are combined. The main objective of bilingual learning at SMP ZIIS Cilongok is to improve foreign language skills, as a provision for seeking experience in visiting abroad, and to develop foreign languages. The research approach used is a qualitative approach with descriptive methods. Data collection methods in this study using interviews and observation. Based on the results of research on the implementation of bilingual learning management, the main thing is the preparation and implementation of learning activities that refer to the applicable curriculum and infrastructure and support from the school, and the process of implementing bilingual learning carried out at SMP ZIIS Cilongok.